Data archiving, management initiatives and expertise in the Biological Sciences Department, University of Cape Town - Koopman, Margaret Marie (Library and Information Studies Centre (LISC), 2015)
Researchers produce large amounts of data during their research investigations and have a variety of interventions for the management of these data. It has not been the responsibility of academic institutions to manage research data, this responsibility has resided with the researchers and their research units. This investigation attempted to understand how pre-digital, early digital and current digital research data in the Biological Sciences Department at the University of Cape Town had been and is being managed, if researchers had archived any of these data and what their opinions were on sharing their research data. Long-term ecological data are an important component of research in the Biological Sciences Department as researchers wish to understand ecosystem changes such as climate change, the spread of alien species and the impact of humans on land and marine exploitation. It is consequently critical that research data, past and present are properly managed for future research so that meaningful management decisions can be made. Research Data Management and the Research Life Cycle are phrases that are very much in the literature at present as librarians and university administrators grapple with the task of implementing data policies and data repositories. The literature review revealed that although the University of Cape Town may be a somewhat behind other international institutions in engaging with Research Data Management and repositories, investigations have been ongoing in other parts of the world and in the international community the groundwork has already been done. Research data have been the preserve of researchers and they are reluctant to give up control of their hard-earned data, usually the result of hours spent on funding applications, and field or laboratory work. Data sets of sufficient quantity and quality to answer research questions can take a researcher a lifetime to accumulate and they understandably do not wish to make these openly available without the insurance that their work will be acknowledged. The findings of this research project revealed that in the absence of systematic data management initiatives at institutional level, researchers had preserved many long-term data sets and in some instances were archiving with international repositories specific to their data types. The findings resulted in a range of suggested interventions for the support of Research Data Management at the University of Cape Town.